A comprehensive overview of the pharmaceutical properties of Indian coastal sand dune flora: Emphasis on anti-virals - Saravanakumar Vigneshwar; Arjun Kowsalya; Sarah Jency John Kennedy; Praveen Gopi; Dinakarkumar Yuvaraj (Annals of Antivirals and Antiretrovirals - Peertechz Publications, 2023)
Viral infections have an essential function in both humans and other organisms. The persistent rise in viral diseases has made critical damage to human well-being. The present review indicates that viral diseases are been entangled in various cancer developments. Developing safe and effective antiviral medications remains a challenge. As a result, finding therapeutic targets that would interfere with the virus without affecting the host is hard-hitting. The use of natural substances rather than chemicals in the formulation of antiviral medications could significantly minimize the risk of side effects in patients. Coastal dune vegetation is a vital resource, which plays an imperative part in biodiversity. Coastal dunes have various utilizations in restorative and drug development. The drugs from marine are vitally been utilized as medicine due to their substantial antiviral, anticancer, and antimicrobial activities. Though Coastal dunes flora has numerous possessions their antiviral properties are rarely reported. Hence, in this report, we have compiled and highlighted the antiviral properties of 128 Indian coastal dune flora. This review may provide access to a profound understanding of coastal dunes' vegetation resources and their usage in the production of antiviral and anticancer drugs. It may also help to preserve and cultivate these plants.